2017
DOI: 10.1097/sap.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physician Assistants on a Breast Reconstruction Practice

Abstract: In breast reconstruction, PAs primarily enhance the efficiency of plastic surgeons, particularly in the clinic, with downstream clinical and financial gains of an indirect nature for surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…12,13 Other studies quantifying the effects of APPs in field found APPs increase the efficiency of attending surgeons. [14][15][16][17] The investigation of the impact of APPs on resident education, particularly surgical resident education, has been limited. Surveys of both surgical faculty and residents have acknowledged that APPs offer benefits in managing the clinical workload while posing a potential threat to resident education.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Other studies quantifying the effects of APPs in field found APPs increase the efficiency of attending surgeons. [14][15][16][17] The investigation of the impact of APPs on resident education, particularly surgical resident education, has been limited. Surveys of both surgical faculty and residents have acknowledged that APPs offer benefits in managing the clinical workload while posing a potential threat to resident education.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, faculty face constant pressure to be clinically productive, and APPs have been demonstrated to improve surgeon efficiency in multiple studies. [14][15][16][17] APPs, residents, and faculty is the next critical step in this process. Assessing, and then periodically reassessing, the team dynamic as well as satisfaction with the responsibilities of the team members ensures continued satisfaction with these roles over time.…”
Section: Commentmentioning
confidence: 99%
“…Chao et al 14 compared efficiency and financial gains after the introduction of PAs in the practice of two breast reconstruction surgeons at an academic health center. They analyzed the data from 1-year period before and 1-year period after the introduction of PAs.…”
Section: Resultsmentioning
confidence: 99%
“…In this perspective, addition of PAs led to net financial gain of ≈$33,533 per year or $2794 per month. 14…”
Section: Resultsmentioning
confidence: 99%
“…9,[14][15][16] With the integration of physician extenders in surgical specialties, there is a significantly reduced direct physician involvement time in patient care without impacting outcomes. 14,16 This time could be used to increase surgical volume or to increase the number of patients seen in clinics. In addition to physician extenders being significantly beneficial on the overall impact on productivity, the financial gains may also offset employment cost.…”
Section: Discussionmentioning
confidence: 99%